Ketika Mendidik Anak dengan Kekerasan Tak Lagi Efektif: Meninjau Kembali Teks-teks Corporal Punishment pada Anak dalam Kitab Amsal Menggunakan Lensa Psikologis dalam Konseling Pastoral - Gernaida Krisna R. Pakpahan; Eunike Wirawan; Andreas L. Rantetampang (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2023)
Children are in the most vulnerable position to experience injustice, neglect, suffering, and violence. Corporal punishment is a form of physical discipline, such as whipping or hitting, considered acceptable as a punishment for transgressions. Many religious figures, parents, and teachers justify this form of discipline, viewing it as a right of authority, sanctioned by the Book of Proverbs. Certain verses in the Book of Proverbs (e.g., Prov. 10:13; 13:24; 14:3; 23:13-14; 26:3) appear to legitimize education through violence on children. This stance appears to contradict research findings over the decades, stating that physical punishment yields more harm than good. This article attempts to revisit the verses on child violence in the Book of Proverbs using a psychological lens in pastoral counseling studies. Employing inductive reasoning and hermeneutics, it will be shown that corporal punishment verses in the Book of Proverbs fundamentally have a cultural context of their time and should be approached with caution in contemporary application. This is also due to psychological studies indicating that violence towards children, possibly intended as a form of education, leads to negative effects on their psychological development. Thus, the research thesis statement is that texts on child violence in the Book of Proverbs, when viewed through a psychological lens in pastoral counseling, necessitate a reevaluation of how parents educate children without violence.